Exits from and returns to welfare benefit receipt in Germany: Cumulative disadvantages or a different kettle of fish? - Torsten Lietzmann; Katrin Hohmeyer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
In 2005, Germany introduced the integrated welfare benefit 'unemployment benefit II' for needy individuals capable of working and their families. In line with international trends, the benefit system is characterised by a broad definition of eligibility and a focus on labour market integration through activation. The heterogeneous recipient groups comprise not only unemployed individuals but also, e.g. low-wage and part-time workers and recipients with family responsibilities. Not only individual employment take-up can enable exits from benefit receipt, but also changes in household composition or household income. A considerable share of exits is only temporary, i.e. former recipients become dependent on benefits again after a short time. Using rich administrative data and estimating discrete-time hazard rate models, we analyse non-employed benefit recipients' chances to exit from and to remain independent of benefit receipt considering different exit routes. We find that employment-related exits from benefit receipt are more stable than others are. Labour market resources are important particularly for employment-related exits, but do not safeguard former recipients from returning to benefit receipt. Among sociodemographic characteristics, cumulative disadvantages for foreign citizens and for the labour market integration of older recipients emerge in that they are associated with low exit and high return probabilities. The results call for differentiated measures addressing not only specific subgroups but also different exit strategies. – – Im Jahr 2005 wurde in Deutschland die integrierte Sozialleistung "Arbeitslosengeld II" für erwerbsfähige Hilfebedürftige und deren Familien eingeführt. Im Einklang mit internationalen Trends ist das Leistungssystem durch eine breite Definition der Anspruchsberechtigung und einen Schwerpunkt auf der Arbeitsmarktintegration durch Aktivierung gekennzeichnet. Die heterogenen Empfängergruppen umfassen nicht nur Arbeitslose, sondern z.B. auch Geringverdiener, Teilzeitbeschäftigte und größere Familien. Nicht nur die individuelle Aufnahme einer Beschäftigung kann den Ausstieg aus dem Leistungsbezug ermöglichen, sondern auch Veränderungen in der Haushaltszusammensetzung oder im Haushaltseinkommen. Ein beträchtlicher Teil der Ausstiege ist nur vorübergehend, d. h. ehemalige Leistungsbeziehende sind nach kurzer Zeit wieder auf Leistungen angewiesen. Unter Verwendung umfangreicher administrativer Daten und durch Schätzung diskreter Verweildauermodelle analysieren wir die Chancen von nicht erwerbstätigen Leistungsbeziehenden, aus dem Leistungsbezug auszusteigen und unabhängig davon zu bleiben, wobei wir verschiedene Ausstiegswege berücksichtigen. Wir stellen fest, dass beschäftigungsbezogene Ausstiege aus dem Leistungsbezug stabiler sind als andere. Arbeitsmarktressourcen sind vor allem für einen beschäftigungsbezogenen Ausstieg wichtig, schützen ehemalige Leistungsbeziehende aber nicht unbedingt vor einer Rückkehr in den Leistungsbezug. Unter den soziodemografischen Merkmalen zeigen sich kumulative Nachteile für ausländische Staatsangehörige und für die Arbeitsmarktintegration älterer Leistungsempfänger, da sie mit niedrigen Ausstiegs- und hohen Rückkehrwahrscheinlichkeiten verbunden sind. Die Ergebnisse erfordern differenzierte Maßnahmen, die nicht nur auf bestimmte Untergruppen, sondern auch auf unterschiedliche Ausstiegsstrategien abzielen.
Keywords: I38; J64; J68; 330; cumulative disadvantage; employment; recidivism; survival analysis; welfare benefits